Neutrophils and their role in the aetiopathogenesis of type 1 and type 2 diabetes. Issue 1 (18th July 2021) - Giovenzana, Anna; Carnovale, Debora; Phillips, Brett; Petrelli, Alessandra; Giannoukakis, Nick
Abstract: Multiple and complex aetiological processes underlie diabetes mellitus, which invariably result in the development of hyperglycaemia. Although there are two prevalent distinct forms of the disease, that is, type 1 and type 2 diabetes, accumulating evidence indicates that these syndromes share more aetiopathological mechanisms than originally thought. This compels a rethinking of the approaches to prevent and treat the different manifestations of what eventually becomes a hyperglycaemic state. This review aims to address the involvement of neutrophils, the most abundant type of granulocytes involved in the initiation of the acute phase of inflammation, in the aetiopathogenesis of diabetes mellitus, with a focus on type 1 and type 2 diabetes. We review the evidence that neutrophils are the first leucocytes to react to and accumulate inside target tissues of diabetes, such as the pancreas and insulin‐sensitive tissues. We then review available data on the role of neutrophils and their functional alteration, with a focus on NETosis, in the progression towards clinical disease. Finally, we review potential approaches as secondary and adjunctive treatments to limit neutrophil‐mediated damage in the prevention of the progression of subclinical disease to clinical hyperglycaemia.